Relationship between the relative age effect and anthropometry, maturity and performance in young soccer players - Gil, S. M.; Badiola, A.; Bidaurrazaga-Letona, I.; Zabala-Lili, J.; Gravina, L.; Santos-Concejero, J.; Lekue, A.; Granados, C. (Journal of Sports Sciences, 2014)
The presence of the relative age effect (RAE) has been widely reported; however, its underlying causes have not yet been determined. With this in mind, the present study examined if anthropometry and performance were different amongst older and younger soccer players born in the same year. Eighty-eight young soccer players participated in the study (age 9.75 ± 0.30). Anthropometric measurements, physical tests (sprint, agility, endurance test, jump and hand dynamometry) and the estimation of the maturity status were carried out. Most players (65.9%) were born in the first half of the year. Older players were taller (P < 0.05), had longer legs (P < 0.01) and a larger fat-free mass (P < 0.05). Maturity offset was smaller in the older boys (P < 0.05); however, age at peak height velocity was similar. Older boys performed better in velocity and agility (P < 0.05) and particularly in the overall score of performance (P < 0.01). Stepwise regression analysis revealed that chronological age was the most important variable in the agility test and the overall score, after the skinfolds (negative effect). We report differences in anthropometry and physical performance amongst older and younger pre-pubertal soccer players. These differences may underlie the RAE.